Conference Review: A Weekend in Leiden: Knitting History Symposium, 2019 - Christine Carnie (EXARC, 2020)
This Conference was organised by the TRC Leiden and the Knitting History Forum in Leiden. On the 2nd of November 2019 I had the opportunity to visit Leiden to take part in the Knitting History Symposium. What follows are my notes and observations and therefore may not accurately reflect what was said. I am very much hoping that the different papers will with time be published and made accessible.